Brucella endocarditis of the aortic valve - Leandro, J (1998)
Brucella endocarditis was diagnosed in two patients with acute renal failure. Both patients had major aortic insufficiency, congestive cardiac failure and clinical and laboratory signs of an active infection, although adequate antibacterial therapy had already been introduced. Replacement of the aortic valve, together with the aortic root in one of the cases, were carried out as emergency procedures, followed by antibacterial treatment with rifampicin, doxycycline and co-trimoxazole. Both patients left the hospital cured and are well 2.5 and 2 years after the surgery, respectively.